2009
DOI: 10.1038/pcan.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Can residents perform transrectal ultrasound-guided prostate biopsy with patient comfort comparable to biopsy performed by attending staff urologists?

Abstract: Transrectal ultrasound (TRUS)-guided prostate biopsy is a critical diagnostic tool in urology. Residents require adequate training but resident education could have a deleterious effect on patient comfort and morbidity. We compared pain associated with prostate biopsy when performed by staff versus resident urologists in order to determine the impact of resident training. Male patients scheduled to undergo prostate biopsy were assigned to either a staff urologist or a resident as the primary surgeon. All resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…When comparing patient-reported comfort in transrectal ultrasound-guided biopsies performed by senior urologist-supervised residents and by attending staff urologists alone, CT Nguyen et al showed that under senior supervision and after a proper amount of training, urology residents can perform the procedure without causing higher levels of discomfort to the patients when compared to those performed by senior urologists [35].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing patient-reported comfort in transrectal ultrasound-guided biopsies performed by senior urologist-supervised residents and by attending staff urologists alone, CT Nguyen et al showed that under senior supervision and after a proper amount of training, urology residents can perform the procedure without causing higher levels of discomfort to the patients when compared to those performed by senior urologists [35].…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear need for more consistent and standardised training in prostate biopsy techniques, as evidenced by trainee feedback, 5 and the findings of this study and that by Hori et al 13 This need is made more acute by the fact that patients tend to experience more discomfort when biopsied by trainees. 25 Similar to any other surgical procedure, case selection should form an integral part of prostate biopsy training. Our data and those of Hori et al 13 suggest that trainees should focus their practice on patients with serum PSA levels of ≥10ng/ml as diagnostic outcomes for initial extended pattern TRUS guided biopsies in this patient group are similar for novices and experienced operators.…”
Section: Implications For Trainingmentioning
confidence: 99%